Design and High Expression of Non-glycosylated Lysostaphins in Pichia pastoris and Their Pharmacodynamic Study - Shen, Wenluan; Yang, Na; Teng, Da; Hao, Ya; Ma, Xuanxuan; Mao, Ruoyu; Wang, Jianhua (Frontiers in Microbiology, 2021)
Lysostaphin is an effective antimicrobial agent to Staphylococcus, especially for the methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Staphylococcus aureus (MDRSA). In this study, the seven lysostaphin derived mutants (rLys) were designed to overcome the barrier of glycosylation during expression in Pichia pastoris. Among them, 127A and 127A232Q had highest antimicrobial activity (MIC values 0.07-0.3 μM) to S. aureus than others and the commercial lysostaphins (1-15.8 times). There was no glycosylation during the expression in 5-L fermenter level, with the high yield of 1315 mg/L (127A) and 1141 mg/L (127A232Q), respectively. Meanwhile, 127A and 127A232Q effectively killed 99.9% of S. aureus at low concentration (1×MIC) within 30min, without the regrowth of pathogen. They also showed low toxicity, high pH and temperature stability. The results of in vivo therapeutic effect of 127A and 127A232Q against high virulent S. aureus CVCC546 showed that 127A and 127A232Q increased the survival rate of infected mice up to 100% at the dose of 10 mg/kg than the untreated group, reduced the bacterial translocation by 5-7 log CFU (over 99%) in organs compared to the untreated group and alleviated multiple-organ injuries (liver, kidney and spleen). These data indicated that the nonglycosylated lysostaphin 127A and 127A232Q may be a promising therapeutic agent against MDR staphylococcal infections